Pengaruh Promosi dan Kuaitas Pelayanan Terhadap Keputusan Pembelian Pada PT King Express Solution Tangerang Selatan - Muhammad Gandung; Adjie Nurrohman (LAP4B, 2025)
The purpose of this study is to determine the influence of promotion and service quality on purchasing decisions at PT King Express Solution. The sample in this study was 89 respondents. Data analysis techniques used include data instrument tests consisting of (validity tests, reliability tests), classical assumption tests consisting of (normality tests, multicollinearity tests, autocorrelation tests, heteroschidasticity tests), simple and multiple linear regression analysis tests, correlation coefficient analysis tests, determination coefficient analysis tests, and partial and simultaneous hypothesis tests. Simple regression equation, Y = 5.313 + 0.547 X1, Y = 6.639 + 0.458 X2, the result of multiple regression equation Y = 6.639 + 0.458 X1 + 0.312 X2. The effect of partial promotion with a value of t = 6.337, there is an influence of partial service quality with a value of t = 7.041, there is an influence of promotion and service quality simulta with a value of F = 30.340. Overall promotions and service quality influenced purchasing decisions by 41.1% while 36.3% were influenced by other variables. It can be concluded that promotion and service quality affect purchasing decisions at PT King Express Solutio South Tangerang